A Concise and Practical Framework for the Development and Usability Evaluation of Patient Information Websites - Peute, L.W.; Knijnenburg, S.L.; Kremer, L.C.; Jaspers, M.W.M. (Applied Clinical Informatics, 2015)
Background: The Website Developmental Model for the Healthcare Consumer (WDMHC) is an extensive and successfully evaluated framework that incorporates user-centered design principles. However, due to its extensiveness its application is limited. In the current study we apply a subset of the WDMHC framework in a case study concerning the development and evaluation of a website aimed at childhood cancer survivors (CCS).Objective: To assess whether the implementation of a limited subset of the WDMHC-framework is sufficient to deliver a high-quality website with few usability problems, aimed at a specific patient population.Methods: The website was developed using a six-step approach divided into three phases derived from the WDMHC: 1) information needs analysis, mock-up creation and focus group discussion; 2) website prototype development; and 3) heuristic evaluation (HE) and think aloud analysis (TA). The HE was performed by three double experts (knowledgeable both in usability engineering and childhood cancer survivorship), who assessed the site using the Nielsen heuristics. Eight end-users were invited to complete three scenarios covering all functionality of the website by TA.Results: The HE and TA were performed concurrently on the website prototype. The HE resulted in 29 unique usability issues; the end-users performing the TA encountered eleven unique problems. Four issues specifically revealed by HE concerned cosmetic design flaws, whereas two problems revealed by TA were related to website content.Conclusion: Based on the subset of the WDMHC framework we were able to deliver a website that closely matched the expectancy of the end-users and resulted in relatively few usability problems during end-user testing. With the successful application of this subset of the WDMHC, we provide developers with a clear and easily applicable framework for the development of healthcare web-sites with high usability aimed at specific medical populations.Citation: Peute LW; Knijnenburg SL; Kremer LC; Jaspers MWM. A concise and practical framework for the development and usability evaluation of patient information websites. Appl Clin Inf 2015; 6: 383–399http://dx.doi.org/10.4338/ACI-11-RA-0109
Keywords: Patient education; childhood cancer; survivorship; website; human factors